If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 55 + y = 2x Solving 55 + y = 2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-55' to each side of the equation. 55 + -55 + y = -55 + 2x Combine like terms: 55 + -55 = 0 0 + y = -55 + 2x y = -55 + 2x Simplifying y = -55 + 2x
| 5b-3-b=18 | | 13n+20=-11n+38 | | 8.1x+81=65.61+9x | | 61+4y-24=13y-12-2y | | 3.34x+33.4=66.8 | | 24x(34+48)=x | | -3z=-24 | | 7x+9y=54 | | x-3/x=4/5 | | -3=.5(4)+5 | | 4x+32=6x+2 | | 50x^2+25a-3=0 | | 5(4x-2)+9=2(8x-7) | | x+13=-22 | | h(x)=-2x+3 | | 4[x+2(3x-7)]=22x-65 | | -5y+5x=35 | | 6x-2(3x-5)=10 | | 2(4R-3)-8=4+2X | | 4a+5a=54 | | x-50=-250 | | y=3*0+9 | | 5x-(x-2)=2x | | 13+x=-26 | | 15*150= | | 0.30x+0.15(110)=0.15(150) | | 3(5x+7)-8=15x+13 | | =(8-4)x+4 | | x^3-4x^2-x+4= | | -4x+8=-7-y | | 3x-2+3-4w+x-w+1+2y+1=22 | | 3x+-x=5x |